1999
DOI: 10.1046/j.1439-0418.1999.00333.x
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of cotton leafworm Spodoptera litura, flower beetle Mylabris pustulata and red cotton bug Dysdercus cingulatus by Rhynocoris marginatus (Fabr.) (Het., Reduviidae) in cotton field cages

Abstract: Mass‐reared reduviid, Rhynocoris marginatus was released in large‐sized cotton field cages against three cotton pests, Spodoptera litura, Mylabris pustulata and Dysdercus cingulatus. Pest species were introduced into separate cages in the absence of other pests, parasitoids and predators. Control experimental cages without R. marginatus were maintained for each prey set up during the evaluation period. R. marginatus greatly reduced the infestation of S. litura (57.5%), M. pustulata (52.3%) and D. cingulatus (4… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…Rhynocoris kumarii Ambrose and Livingstone has been reported to feed on the groundnut pests in the laboratory (Sahayaraj 1994;Sahayaraj & Sivakumar 1995). Ambrose and Claver (1999) and Claver and Ambrose (2001) released R. kumarii in cotton and pigeon pea field cages respectively and evaluated the pest suppression by the predator. However, no report was available on the augmentative release of this predator in the groundnut field and the subsequent impact on groundnut production.…”
Section: Evaluation Of Reduviid Predators and Plant Products Against mentioning
confidence: 99%
See 1 more Smart Citation
“…Rhynocoris kumarii Ambrose and Livingstone has been reported to feed on the groundnut pests in the laboratory (Sahayaraj 1994;Sahayaraj & Sivakumar 1995). Ambrose and Claver (1999) and Claver and Ambrose (2001) released R. kumarii in cotton and pigeon pea field cages respectively and evaluated the pest suppression by the predator. However, no report was available on the augmentative release of this predator in the groundnut field and the subsequent impact on groundnut production.…”
Section: Evaluation Of Reduviid Predators and Plant Products Against mentioning
confidence: 99%
“…Claver and Ambrose (2001) released R. kumarii in a cotton field and it significantly reduced the lepidopteran pests. The field cage release of R. kumarii also suppressed the pest population (Ambrose & Claver 1999). The field release of P. plagipennis (Grundy & Maelzer 2000) and P. laevicollis (Antony et al 1979) were successful in reducing various pests in their released fields.…”
Section: Predator Releasementioning
confidence: 99%
“…Among predatory reduviids, Rhynocoris marginatus (Fabr.) was reported as one potential predator of a variety of cotton insect pests ( Ambrose , 1996; Ambrose and Claver , 1999). The effectiveness of a predator depends on both the speed and sensitivity of its searching behaviour ( Awan , 1988; Kareiva , 1990).…”
Section: Introductionmentioning
confidence: 99%
“…It also provided sufficient prey and niches for the predator and increased the chances of copulation. Compared with other rearing techniques proposed previously, an MEC can easily be adapted to allow for the rearing of this predator (>500 reduviid predators per cage) and made at a low cost (INR 3000–5000 or $US 45–75 per 1000 predators). In addition, the MEC has a compact shape and size, so it is handy and can be placed in a small area and easily carried to the field for predator release.…”
Section: Discussionmentioning
confidence: 99%
“…In a different study, Ambrose and Claver investigated the efficacy of different substrates (untreated plastic; tissue and zigzag‐folded papers; sand and stone; dry litter with strips; green leaves with stems) for the mass production of a reduviid predator, Rhynocoris marginatus (Fab. ), and found that the stadium periods for nymphal instars of R. marginatus reared on dry litter with strips and green leaves with stems were significantly reduced compared with untreated plastic, tissue and zigzag papers and sand with stone substrata.…”
Section: Introductionmentioning
confidence: 99%